Targeting the KRT16-vimentin axis for metastasis in lung cancer - Wen Wang; Lifei Zhu; Jiao Zhou; Xiaoli Liu; Mei Xiao; Nan Chen; Xiaodan Huang; Hongtao Chen; Xiaofeng Pei; Hongyu Zhang (Elsevier, 2023)
Lung cancer is the most diagnosed malignant cancer and the leading cause of cancer-related deaths worldwide, with advanced stage and metastasis being a major issue. The mechanism leading to metastasis is not yet understood. Here, we found that KRT16 is upregulated in metastatic lung cancer tissues and correlated with poor overall survival. Knockdown of KRT16 inhibits metastasis of lung cancer both in vitro and in vivo. Mechanistically, KRT16 interacts with vimentin, and depletion of KRT16 leads to downregulation of vimentin. KRT16 acquired its oncogenic ability by stabilizing vimentin, and vimentin is required for KRT16-driven metastasis. FBXO21 mediates the polyubiquitination and degradation of KRT16, and vimentin inhibits KRT16 ubiquitination and degradation by impairing its interaction with FBXO21. Significantly, IL-15 inhibits metastasis of lung cancer in a mouse model through upregulation of FBXO21, and the level of IL-15 in circulating serum was significantly higher in nonmetastatic lung cancer patients than in metastatic patients. Our findings indicate that targeting the FBXO21/KRT16/vimentin axis may benefit lung cancer patients with metastasis.